The Influence of Hedonic Shopping Motivation and Shopping Lifestyle on Generation Y Impulse Buying At Tiktok Shop in Batam City - Rosmini Rosmini; Yunisa Oktavia (Jurnal Indonesia Sosial Teknologi, 2024)
Technological developments affecting business services. Along with the technological developments that are taking place, there has also been a change in generational growth, namely Generation Y (Millennials). Generation Y (millennials) are familiar with the use of technology, especially on online shopping platforms (e-commerce), and they have different lifestyles and character traits. The convenience offered by one of the e-commerce TikTok shops causes users to make spontaneous purchases. This study aims to determine the effect of hedonic shopping motivation and shopping lifestyle on impulse buying among Gen Y in TikTok Shop in Batam City. The research uses Google Forms as a questionnaire to obtain primary data. The partial research results on the hedonic shopping motivation variable obtained a t-value of 2.354> t table 1.661 and a significant value of 0.021 <0.05. The shopping lifestyle variable received a t-value of 3.199> t table 1.661 and a substantial value of 0.002 <0.05. At the same time, f-count 33.184> f-table 3.09 and a substantial value of 0.000 <0.05. It can be concluded that hedonic shopping motivation and lifestyle positively and significantly affect impulse buying.